2015
DOI: 10.1891/2168-6653.29.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Core Self-Evaluations as a Mediator Between Functional Disability and Life Satisfaction in College Students With Disabilities Majoring in Science and Technology

Abstract: Purpose: To examine the mediational effect of core self-evaluations (CSE) on the relationship between functional disability and life satisfaction.Methods: A quantitative descriptive design using multiple regression analysis. The participants were 97 college students with disabilities receiving services through Hunter College’s Minority-Disability Alliance (MIND Alliance) in science, technology, engineering, and mathematics.Results: CSE was a partial mediator between functional disability and life satisfaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…A second major finding of this study was that it provides further support for the relationship between CSE and life satisfaction. Smedema and colleagues (2014) and Smedema and Tansey (in press) both reported a significant relationship between CSE and life satisfaction among individuals with disabilities. While the association between the two variables was fully mediated by perceived stress and affect in the Smedema et al study, CSE in the current study was found to have a direct relationship with life satisfaction as well as an indirect relationship that is partially mediated by agency thinking and community participation.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A second major finding of this study was that it provides further support for the relationship between CSE and life satisfaction. Smedema and colleagues (2014) and Smedema and Tansey (in press) both reported a significant relationship between CSE and life satisfaction among individuals with disabilities. While the association between the two variables was fully mediated by perceived stress and affect in the Smedema et al study, CSE in the current study was found to have a direct relationship with life satisfaction as well as an indirect relationship that is partially mediated by agency thinking and community participation.…”
Section: Discussionmentioning
confidence: 88%
“…407–414) argues that CSE has great potential as a global positive contributor to subjective well-being in persons with disabilities. Smedema and colleagues (Smedema et al, 2014; Smedema & Tansey, in press), in two recent studies, have begun to investigate the relationship between CSE and life satisfaction in persons with disabilities. Smedema et al (2014), using a sample of undergraduate students with disabilities majoring in science, technology, engineering, and mathematics fields, found a significant positive relationship between CSE and life satisfaction (β = .48, p < .001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, little research has been conducted thus far that has directly investigated the relationship of CSE and well-being in PWDs. Recently, Smedema et al (2014) completed the first study on CSE in PWDs. Smedema and colleagues, using a sample of college students with disabilities, found a significant positive relationship between CSE and life satisfaction (β = .48, p < .001).…”
mentioning
confidence: 99%
“…As with stress, this may be explained by the limited research conducted on nondisclosing students with AND (see Grimes et al, 2017). Future research which seeks to understand traits such as self-efficacy for students with AND may aid university support services to target assistance in such a way as to bolster student success and aid students' subjective well-being (Smedema et al, 2015).…”
Section: Students' Academic Self-efficacy In Higher Educationmentioning
confidence: 99%